Auto (formação) e saberes de docentes de cursos técnicos profissionalizantes de nível médio - Oliveira, Wagner de Moura (2021)
This dissertation is part of the line of research Teacher Training for Professional and Tec hnological Education, from the Academic Master's Degree in Professional and Technological Education at the Federal University of Santa Maria (UFSM). This research sought to understand the understanding of (self) training and teaching knowledge experienced by teachers in the technical areas of Professional and Technological Education (EFA) in the context of pedagogical practice, considering the dialogue between being and becoming a teacher. In the case of technical training, it will be important to understan d the needs of these teachers in the educational contexts in question. The general objective of this research was to elucidate how the (self) training and knowledge of teachers in the technical areas of the Colégio Técnico Industrial de Santa Maria (CTISM) of the Federal University of Santa Maria is constituted. As specific objectives: to analyze how the training process of the technical professors of the professional courses of the Technical College of Santa Maria of the Federal University of Santa Maria UFSM is constituted; analyze and verify the motivational factors that led the teacher of technical courses at the Colégio Técnico Industrial de Santa Maria of the Federal University of Santa Maria UFSM to enter and remain in the teaching career; to anal yze the relationship between the initial and continuing training of teachers who work in courses in areas that are in constant technical transformation. The methodology which was used in the research was done first through a systematic literature review, l ooking for theories and concepts relevant to the research topic in question, encouraging its methodological contributions. Furthermore, it was used indicative points pointed out by teachers' testimonies, collected through the application of a questionnaire with open and closed questions. The locus of the study was the Colégio Técnico Industrial de Santa Maria of the Federal University of Santa Maria UFSM. As a result of the research, it was noticed that their life trajectories refer to their initial traini ng, which is more technical than pedagogical, which shows us that at no time in their initial training they had contact with the pedagogical area, many sought this contact after initial training, because, there was a need to absorb pedagogical knowledge, a s well as all its structures for a good professional development within the classroom.